Competencia Científica y Resolución de Problemas de Física - Carrascosa-Alís, Jaime; Martínez, Salvador; Alonso, Manuel (Revista Científica, 2020)
Boosting and developing scientific competence among students studying subjects such as Physics is an objective currently contemplated in an explicit way in most school curricula and is shared by many experts in Science education. However, when this topic is discussed with science teachers, it is usually done by ignoring the specific contents of the subject to be taught, so that teachers can hardly transfer to their classes what has been exposed to them in terms that are too general. In our opinion, if to promote and develop scientific competence is really wanted, this must be done jointly through key content for the teaching and learning of science, such as the introduction of concepts, problem-solving, and laboratory experiments. The problem is that most science teachers admit that many of the methodological aspects inherent in scientific competence, such as the issuance of hypotheses, the development of strategies for their contrast, the analysis of results, etc., can be incorporated with relative ease to the experimental works, but they do not see it so clear when it concerns the introduction of theoretical concepts or the resolution of pencil and paper problems. This paper attempts to show, through the resolution of a specific Physics problem, how these essential aspects of scientific competence can be contemplated in problem-solving. In addition, the possibility of incorporating practical elements and new technologies, in a functional way, into the resolution is also considered.